2021
DOI: 10.1017/s0022149x21000444
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and seasonal variation of Fasciola hepatica in slaughtered cattle: the role of climate and environmental factors in Mexico

Abstract: The objective of this study is to determine the prevalence of Fasciola hepatica infection in cattle slaughterhouses, as well as its association with climatic/environmental factors (derived from satellite data), seasonality and climate regions in two states in Mexico. Condemned livers from slaughtered animals were obtained from three abattoirs in the states of Puebla and Veracruz. The overall prevalence of the parasite in cattle between January and December of 2017 was 20.6% (1407 out of 6834); the highest rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 31 publications
0
6
0
2
Order By: Relevance
“…Before entering the slaughterhouses, most animals have been grazing in surrounding pastures, while imported breeds are reared through intensive farming breeding systems. It is important to note that the prevalence of cysticercosis may be influenced by various factors, including climate and animal husbandry practices [ 28 ]. Regarding seasonal variation, there is limited information available on the seasonal prevalence of C. bovis in Egypt.…”
Section: Discussionmentioning
confidence: 99%
“…Before entering the slaughterhouses, most animals have been grazing in surrounding pastures, while imported breeds are reared through intensive farming breeding systems. It is important to note that the prevalence of cysticercosis may be influenced by various factors, including climate and animal husbandry practices [ 28 ]. Regarding seasonal variation, there is limited information available on the seasonal prevalence of C. bovis in Egypt.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of more than ten worms in the liver has a sensitivity and specificity of 80%-90% [39][40][41], respectively. As mentioned in the materials and methods section, the feces were collected between November and January (the beginning of winter), when the release of F. hepatica eggs rises [42]. Thus, it is highly probable that more animals tested positive for this parasite.…”
Section: Discussionmentioning
confidence: 99%
“…In slaughterhouse studies show a higher prevalence for F. hepatica due to the presen ce of eggs in the bile content (39.4 %) and lower prevalence due to the presence of adult parasites in the bile ducts (32.4 %) and the egg count (15.5 %) in faeces (Giraldo Forero et al, 2016). However, studies in slaughterhouses show a great variability in results with values as low as 12 % and up to 30 % with the condemnation of livers due to the presence of F. hepat ica (Hernández-Guzmán et al, 2021). The low prevalence of F. hepatica (1 %) in the slaughterhouses of the present study can be associated with the fact that they were the result of samplings carried out at fixed times and not of the systematic registration of all animals that entered the slaughterhouses.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of rumen flukes, there was a five times greater probability of infection in flood-prone areas than in the hills. Environmental conditions have been considered as one of the main factors affecting the distribution of F. hepatica (Hernández-Guzmán et al, 2021), among which the type of soil, precipitation and altitude stand out (Jiménez-Rocha et al, 2017), as confirmed by a study in Bangladesh (Khan et al, 2017). These factors affect the distribution of both liver and rumen flukes and their intermediate host, snails of species as Gal ba truncatula (Jones et al, 2022) Lymnaea glabra (Dreyfuss et al, 2014;Naranjo-Lucena et al, 2018) and in Mexico the presence of Fossaria humilis and F. bulimoides (Cruz-Mendoza et al, 2004) is related with the presence of F. hepatica.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation